The Prosumer's Role as a Driver of Energy Transition: A Study of Individual Power Producers in Jakarta, Indonesia - Noviyanto, Harfiyan -; Sobirin, Ridwan - (Institut Teknologi Bisnis AAS Indonesia, 2025)
The transition to a sustainable energy system is an urgent priority at both global and national levels, aligning with Indonesia's target of achieving Net Zero Emissions (NZE) by 2060. Within this transition, the phenomenon of the